Analysis Of The Influence Of Current Ratio, Debt To Equity Ratio, And Return On Asset On Prices Shares In Property Companies On The Indonesian Stock Exchange Year 2020-2022 - Sri Wanda Sari; Zuwina Miraza; Arasy Ayu Setiamy (Jurnal Ilmu Sosial Mamangan, 2024)
This research was conducted on property companies on the Indonesian Stock Exchange with the aim of research to determine the influence of the current ratio, debt to equity ratio and return on assets partially and simultaneously on share prices. The population of this research was 32 property companies and the samples were taken using purposive sampling so that the total sample was 21 property companies and the number of observations made was 63 observations. This research uses associative and data collection techniques with documentation, and data analysis techniques with multiple linear regression, classical assumption testing and hypothesis testing. Based on the results of research conducted, it shows that partially the current ratio, debt to equity ratio and return on assets have a significant positive effect on the share prices of property companies listed on the IDX. The current ratio, DER and ROA ratio together have a significant effect on share prices in property companies listed on the IDX. There is a strong correlation between the Current ratio, DER and ROA ratio and property company share prices. The size of share prices in property companies can be explained by the Current ratio, DER and ROA ratio, which is 69.8%. Meanwhile, the other 30.2% was influenced by factors not examined in this study